Effectiveness of interactive multimedia utilization in mathematics class VIII SMPN 25 Padang - Putri Amalia Sari; Fetri Yeni J; Meldi Ade Kurnia Yusri (Penerbit Universiti Kebangsaan Malaysia, 2024)
Based on observations made at SMP Negeri 25 Padang in Mathematics, some problems impact the learning outcomes of class VIII students. Researchers found that teachers have not optimised the use of learning media and teaching materials due to limitations in technology or applications. Usually, many students have not reached the minimum completeness criteria set at 75. To overcome these problems, research was conducted using interactive multimedia based on articulate storyline in the learning process. This study aimed to determine the effectiveness of interactive multimedia utilisation on student learning outcomes in Mathematics class VIII SMP Negeri 25 Padang. The research method used in this study was a quantitative quasi-experiment. The population in the study were all grade VIII students in the 2022/2023 academic year. Data was collected from a multiple-choice questionnaire. The results showed that the average value of the experimental class that utilised articulate storyline-based interactive multimedia was 76.17, higher than that of the control class that used textbooks and teaching materials, which was 70.52. It can be concluded that using interactive multimedia based on an articulate storyline effectively affects the learning outcomes of VIII grade students in Mathematics subjects at SMP Negeri 25 Padang.